Low bit-rate subband video coding for tele-monitoring applications - Mohsen Ashourian; Zulkarnain Mohd. Yusof; Syed Abdul Rahman Syed Abu Bakar; Sheikh Hussain Shaikh Salleh, 1958- (Skudai : Universiti Teknologi Malaysia)
40